Hubungan Perilaku Cerdik Terhadap Hipertensi di Puskesmas Kelurahan Pekayon Tahun 2024 - Mochammad Farid Cahya Saputra; Zainal Abidin; Rizka Aries Putranti; Endin Nokik Stujanna; Enrico Adhitya Rinaldi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Hypertension is a non-communicable disease that increases every year. The CERDIK program is one of the non-pharmacological treatments that can be used in an effort to prevent hypertension. This study aims to determine the relationship between smart behavior and hypertension at the Pekayon Village Health Center in 2024. This study uses a quantitative method with a Cross Sectional design. The sample consisted of 96 respondents using Accidental Sampling as the sampling technique. Data analysis used univariate, bivariate, and multivariate analysis. This study shows that at the Pekayon Village Health Center there are 91 people (71.7%) who routinely do health checks. Avoiding cigarette smoke is in the good category as many as 88 people (69.3%), diligently doing physical activity as many as 84% ​​(66.1%), having a balanced diet as many as 88 people (69.3%), getting enough rest as many as 84 people (66.1%), and being able to manage stress well as many as 105 people (82.7%). The results of this study indicate that there is a relationship between CERDIK behavior and hypertension with a p value of <0.05, so there is a correlation between CERDIK behavior and the level of hypertension in patients at the Pekayon Village Health Center.